Produção e composição química de capins do gênero Urochloa (Brs Piatã, Marandú e Xaraés) em diferentes tempos de desfolha - Carvalho, Julio Santos (Brasil, 2024)
The objective of this work was to evaluate the forage production and nutritive value of three cultivars of Urochloa brizantha (BRS Piatã, Marandú and Xaraés) in three functions of various defoliation intervals, introduced in the conditions and edaphoclimatic situations of Parintins-AM. The experiment was conducted in an area of 60 square meters for each cultivar, adopting an entirely randomized design (DIC), in a factorial scheme 3 X 3 (3 cultivars and 3 cutting intervals), with five repetitions. The forage samples were cut at 10 cm from the ground and an area of 0.25 m2 was used as a sampling unit. The cutting intervals evaluated were at 21, 28 and 35 days. The parameters analyzed were: fresh mass, dry mass, plant height, protein fractions, fiber and energy composition and phosphorus, potassium, calcium, magnesium and sulfur contents. The samples were stored in paper bags and , taken to the laboratory of Animal Nutrition of the Institute of Social Sciences, Education and Animal Science (ICSEZ) of the Federal University of Amazonas (UFAM). After drying in an oven for three days at 55°C, the samples were sent for analysis at the laboratory of the Escola Superior de Agricultura Luiz de Queiroz (Esalq-USP), for bromatological analysis using the near infrared reflectance spectroscopy (NIRS) method. The data were submitted to Analysis of Variance (ANOVA) and Tukey's mean test at 5% probability. The forage availability of the cultivars increased with age. The crude protein contents of the cultivars BRS Piatã and Xaraés decreased with age, and increased in the cultivar Xaraés. There was an increase in the contents of neutral detergent fiber (NDF), acid detergent fiber (ADF) and total digestible nutrients (TDI) increased with age in all cultivars.